Screening of actinomycetes from Ninh Thuan and Binh Thuan sea for antimicrobial producers - Vu, Thi Thu Huyen; Le, Thi Hong Minh; Nguyen, Mai Anh; Vu, Thi Quyen; Doan, Thi Mai Huong; Pham, Van Cuong (Vietnam Journal of Marine Science and Technology, 2022)
The sea is a unique ecosystem for finding secondary metabolites from marine microorganisms. Many compounds produced by marine microorganisms with antibacterial activity have been applied in life. Furthermore, microorganisms are renewable raw materials and media for drug production, thus crucial for sustainable development in our life. In this study, we screened for antibacterial activity of microbial strains isolated from tern samples from Ninh Thuan and Binh Thuan seas. The antibacterial activity of the marine microbial crude extracts was performed by the Bioassay method in a 96-well tray. The minimum inhibitory concentration (MIC) test results showed that from 86 strains of microorganisms isolated from the waters of Ninh Thuan and Binh Thuan, 68 strains were able to inhibit the growth of 1 to 6 strains of the tested microorganisms, and 27 over 86 strains had antibacterial activity against at least three strains of microorganisms tested. In which strains G631, G756, G769, and G778 inhibited 4 to 6 tested microorganisms with MIC values equal to or lower than positive controls. Morphological characteristics and molecular biological analysis identified the four most active strains. The results showed that all four strains were actinomycetes.